1994
DOI: 10.1111/j.1365-2141.1994.tb06738.x
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐over pharmacokinetic and thrombogenicity study of a prothrombin complex concentrate and a purified factor IX concentrate

Abstract: A prospective cross-over study was carried out on 19 patients with haemophilia B. comparing the pharmacokinetics of a purified factor IX concentrate prepared by metal chelate affinity chromatography (9MC) with a conventional three-factor prothrombin complex concentrate (9A). The highly purified factor IX concentrate was shown to have a half-life comparable to the PCC; the in vivo recovery of the purified concentrate was significantly greater than that of the complex (P < 0.01). The 20% change in the value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…Consumption coagulopathy and fibrinolysis may be present to different extents and do not necessarily parallel hypercoagulopathy. These findings are consistent with the results of previous work comparing the thrombogenicity of PCCs with highly purified factor IX concentrates in hemophilia B patients [15,17,18]. In our patients, a short peak of elevated markers indicating activation of the coagulation system leading to thrombin formation was observed, but neither prolonged consumption of thrombin nor a parallel increase in fibrinolytic activity could be found.…”
Section: Discussionsupporting
confidence: 93%
“…Consumption coagulopathy and fibrinolysis may be present to different extents and do not necessarily parallel hypercoagulopathy. These findings are consistent with the results of previous work comparing the thrombogenicity of PCCs with highly purified factor IX concentrates in hemophilia B patients [15,17,18]. In our patients, a short peak of elevated markers indicating activation of the coagulation system leading to thrombin formation was observed, but neither prolonged consumption of thrombin nor a parallel increase in fibrinolytic activity could be found.…”
Section: Discussionsupporting
confidence: 93%
“…The in vivo models, in contrast with in vitro assays, clearly differentiate the thrombogenic potential of PCCs from the nonthrombogenic character of HP-FIX concentrates. Thus far, ongo ing clinical studies, using surrogate markers of potential thrombogenicity, also indicate that the HP-FIX products may be less thrombogenic [22][23][24][25]. However, only a con tinued lack of clinical thrombogenicity associated with these products will confirm this hypothesis.…”
Section: Validity Of In Vivo Modelsmentioning
confidence: 58%
“…Several studies by Mannucci et al [35,36], Tho mas et al [37], and others showed that highly purified products tested in a few patients caused no postinfusion activation of the coagulation cascade, as indicated by sen sitive markers such as prothrombin fragment] +2, fibrinopeptide A (FPA), factor X activation peptide, fibrin monomers, or D dimers. These markers increased signifi cantly after infusion with crude PCCs [38].…”
Section: Evidence Of Reduced Risk With High-purity Productsmentioning
confidence: 99%